2017
DOI: 10.1111/mcn.12507
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal prepregnancy obesity and breastfeeding duration: Data from a nationwide prospective birth cohort

Abstract: Association of maternal obesity with shorter breastfeeding duration may involve different factors and might be modified by parity. In a national birth cohort, we aimed to estimate the association between prepregnancy body mass index (pBMI) and breastfeeding duration after adjustment for sociodemographic, pregnancy, and other characteristics and assess the effect modification of parity in such associations. In 2012, 3,368 mother-infant dyads were randomly included at birth in the French Epifane cohort. Breastfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
2
13
1
Order By: Relevance
“…Overweight and obese women may not only have a greater risk of adverse perinatal outcomes [13], but may also have more difficulty in continuing to breastfeed after delivery, due to a decreased prolactin secretion response to suckling [14] and delayed lactogenesis II [15]. However, observational studies have been conducted, to determine the possible associations between pre-pregnancy body mass index (pBMI) and breastfeeding practices, and the evidence remains inconclusive [16][17][18][19][20][21]. Less is known about the effects of maternal pre-pregnancy underweight status on breastfeeding behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obese women may not only have a greater risk of adverse perinatal outcomes [13], but may also have more difficulty in continuing to breastfeed after delivery, due to a decreased prolactin secretion response to suckling [14] and delayed lactogenesis II [15]. However, observational studies have been conducted, to determine the possible associations between pre-pregnancy body mass index (pBMI) and breastfeeding practices, and the evidence remains inconclusive [16][17][18][19][20][21]. Less is known about the effects of maternal pre-pregnancy underweight status on breastfeeding behavior.…”
Section: Introductionmentioning
confidence: 99%
“…They mentioned in their study that maternal obesity caused certain problems, such as a decrease in the prolactin level, responding, and delay. Failure in the breastfeeding results in formula feeding, and this increases the future obesity risk (16,17,21). In the study by Mehta et al (28), in which the effect of the maternal obesity on the beginning of breastfeeding and psychological factors was analyzed, it was found that obese and overweight women have four times higher risk of unsuccessful breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…), (f) having no complications in the post-partum period, (g) having no operative vaginal deliveries, (h) having deliveries with elective cesarean because of cephalopelvic disproportion, (i) having no diagnosed psychological problems, (j) being together with the newborn in the postpartum period, and (k) acceptance to participate in the study. As mentioned in the literature, because the birth type, parity, and maternal age might affect the postpartum comfort and breastfeeding, groups were homogenized by their ages and the birth type, and the study was conducted with only primipara mothers (11,(17)(18)(19). During the study conducted between July and December 2014, 337 (22 underweight, 144 normal, 89 overweight, and 82 obese mothers) births took place at the hospital.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers reporting they had very good or excellent health and partners reporting they had excellent health were more likely to intend to breastfeed and to breastfeed for longer than 6 months. Most research that has looked at predictors of breastfeeding and maternal health have focussed on specific health indicators such as maternal obesity (i.e., [ 35 ] or pregnancy health related conditions such as diabetes (i.e., [ 36 ]). We have shown self-reported maternal and paternal health status also to be a useful indicator of intended breastfeeding behaviours.…”
Section: Discussionmentioning
confidence: 99%